Pengaruh Good Corporate Governance dan Kebijakan Dividen terhadap Manajemen Laba - Ayu Dwi Aprilia; Mirna Rosdiana (Jurnal Proaksi, 2026)
Main Objective - This study aims to examine the effect of good corporate governance and dividend policy on earnings management in retail trade subsector companies listed on the Indonesia Stock Exchange for the 2019–2023 period. Method - This study employed a quantitative method with a descriptive approach and purposive sampling technique. Data analysis techniques employed descriptive statistics, classical assumption tests, and multiple linear regression analysis. Main Findings - The results indicate that managerial ownership and the board of commissioners have a positive effect on earnings management, while dividend policy has no effect on earnings management. These results indicate that good corporate governance mechanisms have not been fully effective in suppressing earnings management practices in retail trade subsector companies. Theoretical and Policy Implications - This study implies that companies need to improve the effectiveness of their good corporate governance implementation and increase the transparency of their financial reports to minimize earnings management practices. Research Novelty - The novelty of this study lies in examining the effect of good corporate governance and dividend policy on earnings management in retail trade subsector companies for the 2019–2023 period.